2009
DOI: 10.1001/archinternmed.2008.509
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin, Epinephrine, and Corticosteroids for In-Hospital Cardiac Arrest

Abstract: clinicaltrials.gov Identifier: NCT00411879.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
284
1
29

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(318 citation statements)
references
References 28 publications
4
284
1
29
Order By: Relevance
“…Analyses from three trials [12][13][14] showed RR of shock reversal of 1.42 (95% CI 0.39-5.24), of survival to hospital discharge of 1.96 (95% CI 0.68-5.64), and of good neurological recovery at hospital discharge of 1.45 (95% CI 0.41-5.13) in favor of corticosteroids. Another trial of 268 adults with in-hospital cardiac arrest found an OR of return to spontaneous circulation of 2.98 (95% CI 1.39-6.40) and of survival to hospital discharge with good neurological outcome of 3.28 (95% CI 1.17-9.20) in favor of methylprednisolone (given during resuscitation), and a OR of survival to hospital discharge with good neurological outcome of 3.74 (95% CI 1.20-11.62) in favor of hydrocortisone (given for post-resuscitation shock) [15].…”
Section: Rationalementioning
confidence: 99%
“…Analyses from three trials [12][13][14] showed RR of shock reversal of 1.42 (95% CI 0.39-5.24), of survival to hospital discharge of 1.96 (95% CI 0.68-5.64), and of good neurological recovery at hospital discharge of 1.45 (95% CI 0.41-5.13) in favor of corticosteroids. Another trial of 268 adults with in-hospital cardiac arrest found an OR of return to spontaneous circulation of 2.98 (95% CI 1.39-6.40) and of survival to hospital discharge with good neurological outcome of 3.28 (95% CI 1.17-9.20) in favor of methylprednisolone (given during resuscitation), and a OR of survival to hospital discharge with good neurological outcome of 3.74 (95% CI 1.20-11.62) in favor of hydrocortisone (given for post-resuscitation shock) [15].…”
Section: Rationalementioning
confidence: 99%
“…The prespecified primary outcome was favorable neurocognitive outcome at hospital discharge, defined as cerebral performance category (CPC) of 1 or 2 (26)(27)(28)(29). CPC scale ranges from 1 to 5, with 1 indicating normal function or minor neurocognitive deficit, 2 moderate disability, 3 severe disability, 4 coma/vegetative state, and 5 death or brain death.…”
Section: Primary Outcomementioning
confidence: 99%
“…In a recent single center placebo-controlled trial [31], 100 consecutive patients with in-hospital cardiac arrest were randomized to receive either 1 mg epinephrine or epinephrine plus 20 IU vasopressin per resuscitation cycle for the fi rst fi ve cycles, followed by additional epinephrine if needed. Based on the results of previous observational studies which documented low cortisol levels in patients resuscitated from cardiac arrest, the intervention group received 40 mg methylprednisolone sodium succinate during the fi rst resuscitation cycle.…”
Section: Epinephrine Versus Vasopressin: Results Of Clinical Trialsmentioning
confidence: 99%